Genome-Wide Investigation of the Phospholipase C Gene Family in Zea mays - Zhu, Jiantang; Zhou, Yuanyuan; Li, Jiale; Li, Hui (Frontiers in Genetics, 2021)
Phospholipase C (PLC) are important regulatory enzymes involved in several lipid and Ca2+-dependent signaling pathways. Previous studies have elucidated the versatile roles of PLC genes in growth, development and stress responses of many plants, however, little is known about the evolutionary history and expression patterns of PLC genes in maize. According to the study, five phosphatidylinositol-specific PLC (PI-PLC) and six non-specific PLC (NPC) genes were identified in maize, respectively. The PI-PLC and NPC genes of maize showed close phylogenetic relationship with their homologous genes in the rice and Arabidopsis. Based on the phylogenic relationships to PLC genes in plants, ZmPLC genes can be divided into two subfamilies in which members of the same subfamily showed similar protein sequences, conserved motifs and gene structures, suggesting possible conserved functions. Transient expression of ZmPLC-GFP fusion protein in Arabidopsis protoplasts cells showed that ZmPLCs are multi-localization. Analyses of expression profiles showed that ZmPLC and ZmNPC genes had temporal and spatial specificity and could be induced by various abiotic stresses. Additionally, some ZmPLC genes located in metaQTL regions associated with agronomic traits. This series of studies has certain reference value for the study of the specific functional characteristics of phospholipase C members in maize plant and to provide good candidate targets for the yield and quality of superior maize cultivars.